PENDEKATAN TEKNOLOGI DAN INFORMASI DALAM PERANCANGAN PUSAT INOVASI MOBIL MASA DEPAN - Steven Giovanni; Doddy Yuono (Jurusan Arsitektur dan Perencanaan, 2019)
Millennials are born where the world is modern and sophisticated technology has been introduced to the public where the entertainment industry has increased and is influenced by the internet. Diverse about the nature or characteristics of this generation and most of all this generation has an increase in the use of technology and digital media and prefers to learn something with the use of visuals. Rapid technological developments are very influential in millennial life. One of the things that has a connection with improving technology in this era is in the automotive sector. Manufacturers of car vehicle brands began to compete in issuing the concept of a future car where car vehicles prioritize system technology features and connectivity features. Therefore, the development of car vehicles continues to grow to date from the types of conventional car vehicles to future cars. By creating a car vehicle of the future, this generation can feel satisfaction in driving and can feel the performance or quality of the vehicle and the most important thing is to be able to feel the comfort and pleasure in driving with increasingly sophisticated technological features. With the existing viewpoint, the project for this millennial generation is the